Analysis Of Leading Economic Sectors In Pekanbaru City - Fadhilah, Muhammad Hafiz (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
Identification of leading sectors in an area is the first step in determining a strategic area as an economic center. This identification is carried out using the Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share and Klassen Typology methods. The data used in this study are Gross Regional Domestic Product (GRDP) data from the city of Pekanbaru and Riau Province from 2016 to 2020. The data collection process was carried out using secondary data obtained from the Central Statistics Agency for Pekanbaru City and the Central Statistics Agency for Riau Province. Based on the research results, there are three leading sectors in the city of Pekanbaru, namely the electricity and gas procurement sector, the information and communication sector, the health services sector and social activities. The government's attention can be directed to these leading sectors in order to encourage economic growth in the city of Pekanbaru.